Use of the information analysis for an estimation of the contamination of underground water in Quaternary deposits in Istrinsky region - A. B. Lisenkov; Yu. Yu. Alentev (Известия высших учебных заведений: Геология и разведка)
Brief geological and hydrogeological characteristics of the study area are given. The assessment of the groundwater contamination by lead, nickel, petroleum, nitrates as a result of anthropogenic impacts on the example of Moscow’s water-ice horizon, obtained with the help of information analysis, these water-balance stations Malaya Istra and calculations periormed in the program SurfBall. The role of difierent landscapes in the contamination of least proiected aquifers is assessed. The conclusions about the potential for pollution of the underlying aquifers are done.